Crop Adaptation to Climate Change. - Yadav, Shyam Singh (Wiley, 2011)
A major task of our time is to ensure adequate food supplies for the world's current population (now nearing 7 billion) in a sustainable way while protecting the vital functions and biological diversity of the global environment. The task of providing for a growing population is likely to be even more difficult in view of actual and potential changes in climatic conditions due to global warming, and as the population continues to grow. Current projections suggest that the world's temperatures will rise 1.8-4.0 by 2100 and population may reach 8 billion by the year 2025 and some 9 billion by mi.